2020
DOI: 10.37185/lns.1.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Academic Performance of Medical Students

Abstract: Objective: To determine the perception of medical students about factors affecting academic performance and to associate them with academic performance. Study Design: Cross sectional.Place and Duration of Study: The study was carried out in the Department of Community Medicine at Wah Medical College, Wah Cantt from January 2018 to August 2018.Materials and Methods: After explaining purpose of the study and taking informed consent, questionnaires were distributed to students and collected after two days. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 2 publications
0
11
1
1
Order By: Relevance
“…In this study, it showed that academic performance decreased as the academic year increased from the 1 st year to the final year due to sleep disturbance because study burden increases as the academic year goes from preclinical to clinical year. This result is unvarying with the previous studies [28][29][30].…”
Section: Discussioncontrasting
confidence: 73%
“…In this study, it showed that academic performance decreased as the academic year increased from the 1 st year to the final year due to sleep disturbance because study burden increases as the academic year goes from preclinical to clinical year. This result is unvarying with the previous studies [28][29][30].…”
Section: Discussioncontrasting
confidence: 73%
“…By contrast, a low level of regulatory teaching brings with it higher levels of stress factors in the teaching process (inadequate methodology, unscheduled changes, and less meaningful content) and in the learning process (more anxiety, task overload): this is why it is considered dysregulatory . This is the context where greater stress symptoms appear ( Khan et al, 2020 ). It has therefore been demonstrated, in a precise manner, that factors of the teaching process can constitute either protective or risk factors during the period of university learning ( Vermunt, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The deactivating emotions (boredom and relief) were used in all three levels of self-regulation and across the three situations, appearing to indicate that they show a similar behavioral pattern, less dependent on the specific situation. Previous research has indicated that boredom-as a negative deactivating emotion-has its own behavior and is a precursor to disengagement and burnout [30,80,81]. Negative emotions have also appeared as precursors to risk behaviors, substance abuse and mental health problems [45].…”
Section: Discussionmentioning
confidence: 99%